Therapeutic efficacy of artemether–lumefantrine for the treatment of uncomplicated falciparum malaria in northwest Benin. (December 2016) - Ogouyèmi-Hounto, Aurore; Azandossessi, Christian; Lawani, Souliatou; Damien, Georgia; Tove, Yolande; Remoue, Franck; Gazard, Dorothée
Abstract Background Artemether/lumefantrine (Coartem® ) has been used as a treatment for uncomplicatedPlasmodium falciparum infection since 2004 in Benin. This open-label, non-randomized study evaluated efficacy of artemether–lumefantrine (AL) in treatment of uncomplicated falciparum malaria in children aged 6–59 months in two malaria transmission sites in northwest Benin. Methods A 42-day therapeutic efficacy study was conducted between August and November 2014, in accordance with 2009 WHO guidelines. One-hundred and twenty-three children, aged 6 months to 5 years, with uncomplicated falciparum malaria were recruited into the study. The primary endpoint was parasitological cure on day 28 and day 42 while the secondary endpoints included: parasite and fever clearance, improvement in haemoglobin levels. Outcomes were classified as early treatment failure (ETF), late clinical failure, late parasitological failure, and adequate clinical and parasitological response (ACPR). Results Before PCR correction, ACPR rates were 87 % (95 % CI 76.0–94.7) and 75.6 %, respectively (95 % CI 67.0–82.9) on day 28 and day 42. In each study site, ACPR rates were 78.3 % in Djougou and 73 % in Cobly on day 42. There was no ETF and after PCR correction ACPR was 100 % in study population. All treatment failures were shown to be due to new infections. Fever was significantly cleared in 24 h and approximately 90 % of parasites where cleared on day 1 and almost all parasites were cleared on day 2. Haemoglobin concentration showed a slight increase with parasitic clearance. Conclusion AL remains an efficacious drug for the treatment of uncomplicated falciparum malaria in Benin, although higher rates of re-infection remain a concern. Surveillance needs to be continued to detect future changes in parasite sensitivity to artemisinin-based combination therapy.